Expression profiling of diabetes-related genes in Streptozotocininduced Rat after treatment with herbal mixture extract / Mohd Waznul Adly Mohd Zaidan...[et al.] - Mohd Zaidan, Mohd Waznul Adly; Abd Shukor, Shazwan; Machap, Chandradevan; Othman, Siti Maryam; Kamaruzaman, Rahiniza; Jaganath, Indu Bala (Universiti Teknologi MARA, Perlis, 2016)
Diabetes mellitus type 2 is a metabolic disorder disease that is caused mainly by insulin resistance and relatively lack of insulin being produced which eventually will lead to the hyperglycemia. Since the occurance of diabetes mellitus type 2 have increased markedly, it has become a worldwide problem with obesity and bad lifestyle as the main factor contributing to diabetes mellitus type 2. Synthetic drugs such as metformin are widely used to lower down glucose level and to reduce the occurance of diabetes. However, herbs also have ability to control the occurance of diabetes naturally. Recent study shows that the mixture of Sambung Nyawa (Gynura procumbens) and Dukung Anak (Phyllanthus watsonii) extract was capable to lower down the glucose level in streptozotocin-induced rat after 8 weeks of treatment. Apart from it, the herbal extract mixture was also found to positively regulate a number of genes related to rat’s diabetes. The genes that were positively regulated by herbal extract treatment were involved in insulin resistance, signaling of hormone, vascular response and also genes that involved in glucose and lipid metabolism